Evaluation of Quality Assurance in Nonformal Education Based on the 8 National Education Standards at PKBM Ar-Royyan, Pekanbaru City - Nur Azica Sardi; Rahmat Fahmi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Nonformal education through Community Learning Centers plays a role in improving educational access for communities excluded from formal education. PKBM Ar Royyan Pekanbaru provides equivalency education programs as alternative learning opportunities for learners from diverse backgrounds. Literature review indicates that the quality of nonformal education depends on the implementation of National Education Standards including content standards, process standards, educators, evaluation systems. This study applies a descriptive qualitative literature review supported by secondary data and field data examples such as observation, interviews, learning documentation. Findings show that content standards and process standards have been implemented through curriculum adaptation and participatory learning methods. Tutor quality influences learning effectiveness. Monitoring systems and learning evaluation indicate efforts toward quality control. Conclusion reveals that quality assurance in the PKBM has been implemented adequately with the need for further improvement in supporting aspects.